Kontroversi Bulog Pada Era Orde Baru - Sinuraya, Theresia Br; Sormin, Saucas Alhakiki; Sari , Anisa Ratna (Mutiara: Multidiciplinary Scientifict Journal, 2023)
To handle staple food and food security in the Unitary State of the Republic of Indonesia Bulog is one of those who carry out this task. In the development of the Bulog case, which has been studied throughout its history, Bulog has had many controversies. Most of these cases were KKN (Corruption, Collusion, and Nepotism). This article summarizes several cases of Bulog, including; The Bulog case with PT. Goro Batara Sakti, the Buloggate Bulog case, the Widjanarko Bulog case, the rice import case from Vietnam, and the export case to Africa. The people desire to eradicate corruption from its roots because corruption has burdened the budget. This also often happens at the regional to central levels. Internal and External Bureau of Logistics conducted a study to make Bulog a public company. Its basis, 2003 the revision of the legal basis for Perum Bulog was based on PP RI No. 61. several things can be a factor in reducing KKN practices at Bulog, including; increasing the revolution in the form of gradual reorganization, further increasing control and revising existing systems and procedures within the department so that it can control many benefits compared to things that are not like KKN. By revolutionizing our educational site in character education, so that the culture in Indonesia, which has been ingrained in the KKN culture, becomes more honest and open to the future, Indonesian people will have good ethics and dignity. To monitor Bulog's performance, audit fraud risk management is needed, which is non-financial and financial, so that it can regulate the controls and functions in Bulog's operations as a BUMN in Indonesia.